2018
DOI: 10.1007/s11244-018-0888-3
|View full text |Cite
|
Sign up to set email alerts
|

Operando Spectroscopic Studies of Cu–SSZ-13 for NH3–SCR deNOx Investigates the Role of NH3 in Observed Cu(II) Reduction at High NO Conversions

Abstract: The small pore zeolite chabazite (SSZ-13) in the copper exchanged form is a very efficient material for the selective catalytic reduction by ammonia (NH 3 ) of nitrogen oxides (NOx) from the exhaust of lean burn engines, typically diesel powered vehicles. The full mechanism occurring during the NH 3 -SCR process is currently debated with outstanding questions including the nature and role of the catalytically active sites. Time-resolved operando spectroscopic techniques have been used to provide new level of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Figure a shows the in situ XANES spectra of Cu2.0‐CHA (Table 1) under steady‐state conditions of NH 3 −SCR (1000 ppm NH 3 , 1000 ppm NO, 10 % O 2 ) in a temperature range of 100–500 °C. The relatively low contact time ( W / F =4.6×10 −4 g s cm −3 , W =7.6 mg, F =1000 mL min −1 ), or in other words, high space velocity (SV) conditions in this study will afford lower NO and NH 3 conversion levels than the previously reported in situ or operando XANES measurements of Cu‐zeolite‐catalyzed NH 3 −SCR . Thus, the XANES results in this study, especially at low temperatures, correspond to the oxidation states of Cu under the conditions that NO and NH 3 are sufficiently supplied.…”
Section: Resultsmentioning
confidence: 63%
“…Figure a shows the in situ XANES spectra of Cu2.0‐CHA (Table 1) under steady‐state conditions of NH 3 −SCR (1000 ppm NH 3 , 1000 ppm NO, 10 % O 2 ) in a temperature range of 100–500 °C. The relatively low contact time ( W / F =4.6×10 −4 g s cm −3 , W =7.6 mg, F =1000 mL min −1 ), or in other words, high space velocity (SV) conditions in this study will afford lower NO and NH 3 conversion levels than the previously reported in situ or operando XANES measurements of Cu‐zeolite‐catalyzed NH 3 −SCR . Thus, the XANES results in this study, especially at low temperatures, correspond to the oxidation states of Cu under the conditions that NO and NH 3 are sufficiently supplied.…”
Section: Resultsmentioning
confidence: 63%
“…Acid sites are involved in ammonia adsorption over bridged hydroxyl of the zeolite framework (Brønsted acid sites). NH3 adsorption/activation can also occurs on Cu species [6]. Consequently, ammonia adsorption capacities were evaluated by NH3 adsorption monitored by FTIR to highlight the poisoning effect induced by inorganic compounds deposit over the whole adsorption sites (Cu units and Brønsted acid sites).…”
Section: Minerals Deposits Impact On Chemical Surface Properties Nh3mentioning
confidence: 99%
“…Operando spectroscopic studies have proven to be successful at providing insight into both active sites and intermediate species for NH 3 -SCR. 12,13 Cu-SSZ-13 has been studied extensively under operando conditions with many of the pertinent results outlined in recent reviews. 4,12 For each of the various spectroscopic methods employed, there are limitations when building mechanistic cycles, an example of which is diffuse reectance infrared Fourier transform spectroscopy (DRIFTS), which has been exploited for several in situ NH 3 -SCR studies.…”
Section: Introductionmentioning
confidence: 99%